1968
DOI: 10.1126/science.162.3859.1281
|View full text |Cite
|
Sign up to set email alerts
|

Human Monocytes: Distinct Receptor Sites for the Third Component of Complement and for Immunoglobulin G

Abstract: Human monocytes contain two distinct receptor sites, one specific for the third component of complement (C'3), the other for immunoglobulin G(gammaG). The two receptors may function either independently or cooperatively in the induction of phagocytosis. Ingestion of erythrocytes coated with immunoglobulin M antibody requires a relatively large number of bound C'3 molecules per cell. Ingestion of erythrocytes sensitized with gammaG antibody is independent of complement; however, the reaction is inhibited by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0
1

Year Published

1970
1970
1981
1981

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(125 citation statements)
references
References 13 publications
5
119
0
1
Order By: Relevance
“…Observations on complement requirements for erythrophagocytosis by polymorphonuclear and mononuclear leukocytes have demonstrated that for efficient phagocytosis of red cells, 7S antibody and the first four components of complement are required (21,22). Phagocytosis of pneumococci in the presence of type-specific opsonins and heat-labile factors has recently been reported by Johnston, Klemperer, Alper, and Rosen (23).…”
Section: Discussionmentioning
confidence: 99%
“…Observations on complement requirements for erythrophagocytosis by polymorphonuclear and mononuclear leukocytes have demonstrated that for efficient phagocytosis of red cells, 7S antibody and the first four components of complement are required (21,22). Phagocytosis of pneumococci in the presence of type-specific opsonins and heat-labile factors has recently been reported by Johnston, Klemperer, Alper, and Rosen (23).…”
Section: Discussionmentioning
confidence: 99%
“…According to these authors, complement bound to the antibody within the complexes may sterically hinder or directly bind to the sites on the Ig molecules which have affinity for the lymphocyte membrane. Although soluble aggregates containing complement bind to cells primarily via complement receptors, it should be noted that in other systems it has been shown that receptors for IgG Fc play a significant role in other cell functions such as phagocytosis of EAC' (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in the field of cellular immunology have now permitted differentiations of different types of mononuclear cells (1)(2)(3)(4)(5)(6)(7). Human lymphocytes may be classified, based upon animal experiments and studies in patients with immunodeficiency states, into at least two groupsthymic-dependent lymphocytes (T cells) and thymicindependent or bone marrow-derived lymphocytes (B cells) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). T cells are thought to mediate reactions of cellular immunity, whereas B cells are primarily concerned with humoral immunity (14,15).…”
Section: Immunologic Characterization Of the Mononuclear Cell Infiltrmentioning
confidence: 99%